IMPLEMENTASI PEMBELAJARAN FIQIH DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK PEDULI LINGKUNGAN: (Studi Kasus di Sekolah Adiwiyata MTs Al-Hikam Jatirejo Diwek Jombang) - Moh. Irfan; Abdul Natsir (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2023)
This research aims to describe the implementation of fiqh learning in forming the character of students who care about the environment at the Adiwiyata School MTs Al-Hikam Jatirejo Diwek Jombang. This research includes qualitative research with the type of case study research, namely research that produces descriptive data in the form of spoken or written words at MTs Al-Hikam Jatirejo Diwek Jombang. The data collection technique uses observation, interviews and documentation. Meanwhile, the data analysis uses qualitative descriptive analysis in the style of Miles and Huberman, namely data reduction, data display and drawing conclusions or data verification. The research results show that the condition of the students' environmental care character at MTs Al-Hikam Jatirejo Diwek Jobang is quite good. This is the implementation of fiqh learning in the formation of environmentally caring character. Teachers play an important role in educating students by deepening the material, practicing it, giving examples to all students. The supporting factor is the existence of the adiwiyata program, while the inhibiting factor is the lack of awareness of students regarding the issue of caring for the environment itself.